2017
DOI: 10.1007/s40614-017-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

An Internal and Critical Review of the PEAK Relational Training System for Children with Autism and Related Intellectual Disabilities: 2014–2017

Abstract: The PEAK Relational Training System was designed as an assessment instrument and treatment protocol for addressing language and cognitive deficits in children with autism. PEAK contains four comprehensive training modules: Direct Training and Generalization emphasize a contingency-based framework of language development, and Equivalence and Transformation emphasize an approach to language development consistent with Relational Frame Theory. The present paper provides a comprehensive and critical review of peer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
22
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 75 publications
(75 reference statements)
2
22
0
3
Order By: Relevance
“…To our knowledge, prior research has never demonstrated such a transformation in individuals with autism. Therefore the present study supports the application of this single aspect of the PEAK system, adding to a growing body of research utilizing procedures from this technology (see Dixon et al, for an internal critical review of research on PEAK), but obviously larger scaled studies are still needed to examine the curriculum as a whole.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…To our knowledge, prior research has never demonstrated such a transformation in individuals with autism. Therefore the present study supports the application of this single aspect of the PEAK system, adding to a growing body of research utilizing procedures from this technology (see Dixon et al, for an internal critical review of research on PEAK), but obviously larger scaled studies are still needed to examine the curriculum as a whole.…”
Section: Discussionsupporting
confidence: 67%
“…The procedures were taken from the PEAK Relational Training System (PEAK; Dixon, ), a language development curriculum designed for use with individuals with autism. A standardized curriculum was used to aid in replication by researchers and clinicians that use the programs adapted from PEAK (Belisle, Dixon, Stanley, Munoz, & Daar, ; Dixon et al, ).…”
mentioning
confidence: 99%
“…However, despite its widespread use, there is a paucity of evidence on the VB‐MAPP's psychometrics (see Dixon, Carman, Tyler, Whiting, Enoch et al, ; Gould et al, ) and utility in treatment. By contrast, the last few years have seen a growing body of psychometric and treatment research on the newest language assessment and curriculum tool, the Promoting the Emergence of Advanced Knowledge Relational Training System (PEAK; see also Dixon et al, , for an overview and review).…”
mentioning
confidence: 99%
“…Reed and Luiselli () provided a review of one of the PEAK modules: the PEAK Direct Training module (PEAK‐DTM). PEAK‐DTM is a commercially available curriculum “… designed to assess and teach language skills according to the traditional ABC design in which each response is reinforced in the presence of an appropriate discriminative stimulus” (McKeel, Dixon, Daar, Rowsey, & Szekely, , p. 232; see also Dixon, and Dixon et al, ). The PEAK‐DTM's curricular decisions are derived from scores on the criterion‐referenced PEAK‐DTM Assessment (PEAK‐DTA), which consists of “184 items targeting core learning skills” (Rowsey, Belisle, & Dixon, , p. 18).…”
mentioning
confidence: 99%
“…A second concern, however, is that Witts' review is already dated. At least four research studies on PEAK‐DTM were published following the completion of Witts' review (Belisle, Dixon, & Stanley, ; Dixon, Belisle, Munoz, Stanley, & Rowsey, ; Dixon, Belisle, Stanley, & Rowsey, 2018; Dixon, Wiggins, & Belisle, 2018). We mention these studies from the outset to show that in a rapidly progressive science on any topic, reviews of past work are likely to become dated quickly, as current research builds on prior limitations.…”
mentioning
confidence: 99%